Equine atypical myopathy caused by hypoglycin A intoxication associated with ingestion of sycamore maple tree seeds. (16th July 2015) - Żuraw, A.; Dietert, K.; Kühnel, S.; Sander, J.; Klopfleisch, R.
Summary: Reasons for performing study: Evidence suggest there is a link between equine atypical myopathy (EAM) and ingestion of sycamore maple tree seeds. Objectives: To further evaluate the hypothesis that the ingestion of hypoglycin A (HGA) containing sycamore maple tree seeds causes acquired multiple acyl‐CoA dehydrogenase deficiency and might be associated with the clinical and pathological signs of EAM. Study design: Case report. Methods: Necropsy and histopathology, using hematoxylin and eosin and Sudan III stains, were performed on a 2.5‐year‐old mare that died following the development of clinical signs of progressive muscle stiffness and recumbency. Prior to death, the animal ingested sycamore maple tree seeds (Acer pseudoplatanus) . Detection of metabolites in blood and urine obtained post mortem was performed by rapid ultra‐performance liquid chromatography‐tandem mass spectrometry. Data from this case were compared with 3 geldings with no clinical history of myopathy. Results: Macroscopic examination revealed fragments of maple tree seeds in the stomach and severe myopathy of several muscle groups including Mm. intercostales, deltoidei and trapezii . Histologically, the affected muscles showed severe, acute rhabdomyolysis with extensive accumulation of finely dispersed fat droplets in the cytoplasm of degenerated skeletal muscle cells not present in controls. Urine and serum concentrations of several acyl carnitines and acyl glycines were increased, and both contained metabolites of HGA, a toxic amino acid present in sycamore maple tree seeds. Conclusions: The study supports the hypothesis that ingestion of HGA‐containing maple tree seeds may cause EAM due to acquired multiple acyl‐CoA dehydrogenase deficiency.